1992
DOI: 10.1111/j.1600-0447.1992.tb03249.x
|View full text |Cite
|
Sign up to set email alerts
|

Distressing behaviour of schizophrenics at home

Abstract: The care of mentally ill people at home is being encouraged nowadays. As a result, the family members feel an increased burden of care and find it difficult to cope with the care of a schizophrenic patient at home. We interviewed the relatives of 62 schizophrenics systematically regarding the behaviour of the patients that was perceived to be distressful. This was done using the Scale for Assessment of Family Distress. It was noted that behaviours related to activity and self-care were perceived to be most dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
40
4
5

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 5 publications
8
40
4
5
Order By: Relevance
“…On statistical analysis it was seen that literate caregivers of Chronic Schizophrenia experienced significantly higher burden than the literate caregivers of BPAD. Our finding corresponds with the findings of Gopinath and Chaturvedi 1992 [20] , who also found that caregivers who were educated experienced more burden. Majority of caregivers in both the groups belonged to poor families.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…On statistical analysis it was seen that literate caregivers of Chronic Schizophrenia experienced significantly higher burden than the literate caregivers of BPAD. Our finding corresponds with the findings of Gopinath and Chaturvedi 1992 [20] , who also found that caregivers who were educated experienced more burden. Majority of caregivers in both the groups belonged to poor families.…”
Section: Discussionsupporting
confidence: 81%
“…Caregiver characteristics associated with burden have received comparatively less attention. Women take on a large part of care giving responsibilities [19] and caregivers who are younger and more educated experience greater burden [20] . The relationship of the primary caregiver to the patient may also mediate the experience of burden.…”
Section: Introductionmentioning
confidence: 99%
“…Inability to work, especially for male schizophrenia patients, is associated with a family economic burden. Patients being unable to discharge this role expected of them is a stress factor for themselves and increases the caregiver's economic burden dimension (12,16,33). Patients who are housewives having functional difficulties with housework and being in need of receiving help from outside also exhibits a similar association with caregiver economic burden.…”
Section: Discussionmentioning
confidence: 99%
“…Many people with mental illness are cared for in the community by carers who are unpaid and face many burdens associated with caring for someone with a disability (Gopinath and Chaturvedi, 1992;Randolph et al, 1994). One of the objectives of the National Mental Health Policy (1992) is to support the development and expansion of non-government organizations to assist carers through information provision, and opportunities to participate in mental health service decision-making (Commonwealth Department of Human Services and Health, 1992a).…”
Section: Shift Towards Non-government Organizations As Service Providersmentioning
confidence: 99%